2016
DOI: 10.22159//ijpps.2016.v8i9.10425
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antidiabetic Activity of New Lanostenoids From the Leaves of Psidium Guajava L.

Abstract: <p><strong>Objective: </strong><a href="http://www.webmd.com/diabetes/default.htm">Diabetes</a> mellitus is a chronic metabolic disease which affects our body's ability to use the energy found in food. Our study was planned to isolate chemical constituents from the leaves of <em>Psidium guajava</em> L. (Myrtaceae), to characterize their structures and to investigate their antidiabetic activity.</p><p><strong>Methods: </strong>The air-dried leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The administration of 50 mg/kg of these isolate compounds for 1 week in diabetic rats model showed blood glucose levels of 142.50, 154.50, 165.67, and 172.17 mg/dL, respectively. However, the normal control rat and the diabetic control rat showed 87.66 and 327.33 mg/dL blood glucose levels after 1 week [35]. Several terpenoid compounds have been tested as α-glucosidase inhibitors, including ursolic acid, 3β-hydroxy-11-ursen-28,13-olide, and ursonic acid.…”
Section: Stellasterol In Silico Study For α-Glucosidase Enzymementioning
confidence: 99%
“…The administration of 50 mg/kg of these isolate compounds for 1 week in diabetic rats model showed blood glucose levels of 142.50, 154.50, 165.67, and 172.17 mg/dL, respectively. However, the normal control rat and the diabetic control rat showed 87.66 and 327.33 mg/dL blood glucose levels after 1 week [35]. Several terpenoid compounds have been tested as α-glucosidase inhibitors, including ursolic acid, 3β-hydroxy-11-ursen-28,13-olide, and ursonic acid.…”
Section: Stellasterol In Silico Study For α-Glucosidase Enzymementioning
confidence: 99%
“…The potential antidiabetic activities of Psidium guajava have been demonstrated in Caco-2 cells and diabetic rats models (Hedayathullah-Khan et al 2013;Muller et al 2018). Psidiumlanostenoic acid, 12β-hydroxypsidiumlanostenoic acid, trihydroxypsidiumlanostenoic acid, psidiumlanostenoic acid glucoside, quercetin, isoquercetin, and rutin were considered as the compounds responsible for the antidiabetic activity of this plant (Bagri et al 2016). The antidiabetic related activities of various extracts and fractions of Androgrphis paniculata have been proved in in-vivo and in-vitro studies (Wibudi et al 2008;Chaurasia et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Al-Enazi [27] had reported that a combination, rutin with silymarin had more ameliorative effect on oxidative stress in streptozotocin (STZ)-induced diabetic rats. Since herbal medicines are rich in flavonoids, in recent years they are gaining more importance as a major source of hypoglycemic agents [28]. Flavonoids and polyphenols have been reported to reduce various complications associated with diabetes in liver, kidneys, and blood vessels through mechanisms such as inhibition of aldose reductase, advanced glycation end-products inhibition, and the decrease of oxidative stress [29].…”
Section: Discussionmentioning
confidence: 99%